A new method for volumetric measurement of the normal female cervix by three‐dimensional transvaginal ultrasound. Issue 2 (27th May 2021) - Prka, Matija; Despot, Albert; Brnčić Fischer, Alemka; Haller, Herman; Tikvica Luetić, Ana; Habek, Dubravko
Synopsis: A new and simple method for volumetric measurement of a normal female cervix by three‐dimensional transvaginal ultrasound, using a geometric formula for elliptic cylinders.